MEASURING CUTTING FORCES IN MACHINING PROCESSES - Vásquez Céspedes, Horacio (Ingeniería, 2011)
The principle of operation of force sensors most commonly used in machining processes and the trends of this technology arepresented in this paper. Force sensors are needed because measuring cutting forces during machining processes is the mostimportant and basic step to determine and control the conditions under which the machine, the tool, and the workpiece are performing.In the majority of applications the measurement of cutting forces during machining is done using dynamometers basedon either strain gages or piezo-electric transducer with quartz sensors. Recently, micro-electro-mechanical systems (MEMS) arebeing designed and constructed using polysilicon beam resonators to measure forces. These sensors relate the force that is beingmeasured to the frequency of vibration of the resonator. In recent research projects and studies, there is a tendency to transferthe force sensor signals by wireless technology.